RNA-Seq profiling of circular RNAs in human laryngeal squamous cell carcinomas - Lu, Cheng (Mol Cancer, 2018)
Abnormal expression of non-coding circular RNAs (circRNAs) have been reported in many types of tumors. circRNA have been suggested to be an ideal candidate biomarker for diagnostic and therapeutic implications in cancers. The aim of this study was to assess the circRNA expression profile of laryngeal squamous cell carcinomas (LSCC). The biopsy samples from patients with LSCC were obtained intra-operatively. The circRNA expression was performed using secondary sequencing. Among 10 patients with LSCC, 2 were well differentiated, 3 were moderately differentiated and 5 were adjunctive samples with normal and LSCC tissues. A total of 21,444 distinct circRNA candidates were detected. Among them, we defined the statistical criteria for selecting aberrant-expressed circRNA using a q-value of < 0.001 with a fold change of > 2.0 or < 0.5. A total of 29 circRNA were upregulated and 19 circRNA were downregulated significantly in the LSCC tissues. The intersection of these dysregulated circRNAs of normal-well differentiated set and normal-moderately differentiated set was then assessed to narrow the upregulated and downregulated circRNAs down to 18 and 5 respectively. Furthermore, an association of the circRNA-miRNA-mRNA was investigated, showing that 20 dysregulated circRNA successfully predicted an interaction with several cancer-related miRNAs. Finally, a further KEGG analysis showed that PPAR, Axon guidance, Wnt and Cell cycle signaling pathway were key putative pathways in the process of LSCC. hsa_circ:chr20:31876585–31,897,648 was found to be able to differentiate most of LSCC from the matching normal tissues. This observational study demonstrated dysregulation of circRNA in LSCC, which may have an impact on development of potential biomarkers in this disease. Validation of down-regulation of hsa_circ:chr20:31876585–31,897,648 in LSCC compared to each adjunctive tissue by Q-RT-PCR, indicating that hsa_circ:chr20:31876585–31,897,648 may be a novel promising tumor suppresser in LSCC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12943-018-0833-x) contains supplementary material, which is available to authorized users.